2015
DOI: 10.1121/1.4915475
|View full text |Cite
|
Sign up to set email alerts
|

Generation of random microstructures and prediction of sound velocity and absorption for open foams with spherical pores

Abstract: This paper proposes and discusses an approach for the design and quality inspection of the morphology dedicated for sound absorbing foams, using a relatively simple technique for a random generation of periodic microstructures representative for open-cell foams with spherical pores. The design is controlled by a few parameters, namely, the total open porosity and the average pore size, as well as the standard deviation of pore size. These design parameters are set up exactly and independently, however, the set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Pore-structure characterization is possible using geometrical representation of the porous structure, derived through either simple packing models [30,31] or directly from porous samples using X-ray tomography [15,32], coupled with modelling of transport through these structures. In this way, all the parameters required for the JCAPL model [31] can be estimated.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Pore-structure characterization is possible using geometrical representation of the porous structure, derived through either simple packing models [30,31] or directly from porous samples using X-ray tomography [15,32], coupled with modelling of transport through these structures. In this way, all the parameters required for the JCAPL model [31] can be estimated.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…44 It has been recently reported that such foams have a very complex micro-geometry and exhibit good sound absorbing properties. 45,46 From two specimens of such foam manufactured separately, one with a thickness of approximately 24 mm, the other with a thickness of approximately 18 mm, two cylindrical samples were cut with a diameter of 29 mm (see Fig. 6) to fit inside an impedance tube well.…”
Section: A Inverse Characterization Of a Ceramic Foammentioning
confidence: 99%
“…By using a numerical microstructure-based approach to obtain the non-acoustical parameters used in the JCAPL model, Perrot et al discussed the effects of throat size, pore size and cross-section shape on the sound absorption performance of porous fibrous materials [22] and also evaluated the approach on foams with experimental measurements [23]. By following the same approach, Hoang and Perrot studied the effects of the thin membranes [24] and Zieliński discussed the influences of a microstructure with randomly-distributed spherical pores [25]. On the other hand, the non-acoustical parameters can also be obtained by using semi-phenomenological models.…”
mentioning
confidence: 99%
“…The influences of the geometrical properties and the solid properties are investigated by focusing on the effective material parameters involving both mechanical and acoustical properties of polymer foams. For the geometrical properties, earlier investigations on these factors [22,23,24,25,26,27] were based on the JCAPL model, in which the solid deformation is not considered.…”
mentioning
confidence: 99%